Novel Dosing and Monitoring of Aspirin in Infants With Systemic-to-Pulmonary Artery Shunt Physiology: the SOPRANO Study - Branstetter, Joshua W; Woods, Gary; Zaki, Hania; Coolidge, Nicole; Zinyandu, Tawanda; Shashidharan, Subhadra; Aljiffry, Alaa (The journal of pediatric pharmacology and therapeutics, 2023)
Provision of pulmonary blood flow with a systemic-to-pulmonary artery shunt is essential in some patients with cyanotic congenital heart disease. Traditionally, aspirin (ASA) has been used to prevent thrombosis. We evaluated ASA dosing with 2 separate antiplatelet monitoring tests for accuracy and reliability.OBJECTIVESProvision of pulmonary blood flow with a systemic-to-pulmonary artery shunt is essential in some patients with cyanotic congenital heart disease. Traditionally, aspirin (ASA) has been used to prevent thrombosis. We evaluated ASA dosing with 2 separate antiplatelet monitoring tests for accuracy and reliability.This is a retrospective, pre-post intervention single center study. Two cohorts were evaluated; the pre-intervention group used thromboelastography platelet mapping (TPM) and post-intervention used VerifyNow aspirin reactivity unit (ARU) monitoring. The primary endpoint was to compare therapeutic effect of TPM and ARU with regard to platelet inhibition. Inadequate platelet inhibition was defined as TPM <50% inhibition and ARU >550.METHODSThis is a retrospective, pre-post intervention single center study. Two cohorts were evaluated; the pre-intervention group used thromboelastography platelet mapping (TPM) and post-intervention used VerifyNow aspirin reactivity unit (ARU) monitoring. The primary endpoint was to compare therapeutic effect of TPM and ARU with regard to platelet inhibition. Inadequate platelet inhibition was defined as TPM <50% inhibition and ARU >550.Data from 49 patients were analyzed: 25 in the TPM group and 24 in the ARU group. Baseline characteristics were similar amongst the cohorts. The TPM group had significantly more patients with inadequate platelet inhibition (14 [56%] vs 2 [8%]; p = 0.0006) and required escalation with additional thromboprophylaxis (15 [60%] vs 5 [21%]). There was no difference in shunt thrombosis (1 [2%] vs 0 [0%]; p = 0.32), cyanosis requiring early re-intervention (9 [36%] vs 14 [58%]; p = 0.11), or bleeding (15 [60%] vs 14 [58%]; p = 0.66).RESULTSData from 49 patients were analyzed: 25 in the TPM group and 24 in the ARU group. Baseline characteristics were similar amongst the cohorts. The TPM group had significantly more patients with inadequate platelet inhibition (14 [56%] vs 2 [8%]; p = 0.0006) and required escalation with additional thromboprophylaxis (15 [60%] vs 5 [21%]). There was no difference in shunt thrombosis (1 [2%] vs 0 [0%]; p = 0.32), cyanosis requiring early re-intervention (9 [36%] vs 14 [58%]; p = 0.11), or bleeding (15 [60%] vs 14 [58%]; p = 0.66).With similar cohorts and the same ASA-dosing nomogram, ARU monitoring resulted in a reduced need for escalation of care and concomitant thromboprophylaxis with no difference in adverse outcomes. Our study suggests ARU monitoring compared with TPM may be a more reliable therapeutic platelet inhibition test for determining ASA sensitivity in children with congenital heart disease requiring systemic-to-pulmonary artery shunt.CONCLUSIONWith similar cohorts and the same ASA-dosing nomogram, ARU monitoring resulted in a reduced need for escalation of care and concomitant thromboprophylaxis with no difference in adverse outcomes. Our study suggests ARU monitoring compared with TPM may be a more reliable therapeutic platelet inhibition test for determining ASA sensitivity in children with congenital heart disease requiring systemic-to-pulmonary artery shunt.